Reduction of the mortality to the General surgical department of General hospital Valjevo: Serbia - Vuković Mira H.; Ilić Vladan R. (Srpsko lekarsko drustvo, 2018)
Introduction: The safety of surgical procedures has emerged as a significant global public health problem. Aim: In this study, an assessment was made of the mortality in the population of general surgical patients and is proposed to prevent the occurrence of adverse events involving death. Methods: A study of time series that routinely monitored quality indicators was carried out from January to November 2017, with a special reference to the number of deaths and the total mortality rate at the General Surgery Department GSD, General Hospital Valjevo, Serbia. Results: Hospitalized patients over 65 years of age and prolonged hospitalization of surgical patients positively correlated with the Total mortality rate at the General Surgery Department. The short stay of patients in the Intensive Care Unit of the General Hospital Valjevo significantly reduced the total mortality rate in patients of the General Surgery Department. Conclusion: It is necessary to introduce routine monitoring of new quality indicators that are directly related to the clinical procedures that lead to the reduction of the mortality in general surgical patients.